Proteomic‐based identification of oocyte maturation‐related proteins in mouse germinal vesicle oocytes. Issue 11 (14th October 2020) - Cao, Senyang; Huang, Shaoping; Guo, Ying; Zhou, Lin; Lu, Ying; Lai, Shanshan
Abstract: Oocyte proteins play an important role in oocyte maturation, fertilization and embryonic development. However, the protein composition of mouse germinal vesicle (GV) oocytes is still unclear. Using one‐dimensional Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (1D SDS‐PAGE) and Reverse‐phase liquid chromatography tandem mass spectrometry (RP‐LC‐MS/MS), we constructed a protein profile of mouse GV oocytes. First, our proteomics profile identified 1, 405 different proteins from 11, 000 mouse GV oocytes lacking zona pellucida. Second, with detailed bioinformatics analysis, a group of proteins that play an essential role in oocyte maturation was screened. In addition, the expression and localization of suppressor of G2 allele of skp1(SUGT1, also called SGT1), heterogeneous nuclear ribonucleoprotein K (Hnrpk), Seruin, Cullin1(Clu1) and nuclear distribution protein C (Nudc) in mouse ovaries and early embryos were also captured and investigated in this study. Moreover, the protein profile was submitted to the Proteomics Identifications Database (PRIDE) and is available via ProteomeXchange with the identifier PXD014314. Our research provides valuable resources for the study of oocyte proteins and oocyte maturation and helps to clarify the mechanisms of oocyte maturation.